Hadith #3127 - Sahih al-Bukhari - Abu Jamra Ad-Dabi (Sahih al-Bukhari)
I used to sit with Ibn `Abbas in Mecca. Once I had a fever and he said (to me), âCool your fever with Zamzam water, for Allahâs Messenger (ï·º) said: âIt, (the Fever) is from the heat of the (Hell) Fire; so, cool it with water (or Zamzam water).
Grade: Sahih

Hadith #3373 - Sahih al-Bukhari - Abu Jamra Ad-Dabi (Sahih al-Bukhari)
Ibn `Abbas said to us, âShall I tell you the story of Abu Dharâs conversion to Islam?â We said, âYes.â He said, âAbu Dhar said: I was a man from the tribe of Ghifar. We heard that a man had appeared in Mecca, claiming to be a Prophet. ! said to my brother, âGo to that man and talk to him and bring me his news.â He set out, met him and returned. I asked him, âWhat is the news with you?â He said, âBy Allah, I saw a man enjoining what is good and forbidding what is evil.â I
Grade: Sahih

Hadith #4002 - Sahih al-Bukhari - Abu Jamra Ad-Dabi (Sahih al-Bukhari)
I asked Aidh bin `Amr, who was one of the companions of the Prophet (ï·º) one of those (who gave the allegiance to the Prophet (ï·º) the Tree: âCan the witr prayer be repeated (in one night)?â He said, âIf you have offered it in the first part of the night, you should not repeat it in the last part âof the night.â (See Fath-ul-Bari page 458 Vol 8th).
Grade: Sahih

Hadith #4178 - Sahih al-Bukhari - Abu Jamra Ad-Dabi (Sahih al-Bukhari)
I said to Ibn `Abbas, âI have an earthenware pot containing Nabidh (i.e. water and dates or grapes) for me, and I drink of it while it is sweet. If I drink much of it and stay with the people for a long time, I get afraid that they may discover it (for I will appear as if I were drunk). Ibn `Abbas said, âA delegation of `Abdul Qais came to Allahâs Messenger (ï·º) and he said, âWelcome, O people! Neither will you have disgrace nor will you regret.â They said, âO Allahâs Messenger (ï
Grade: Sahih

Hadith #4911 - Sahih al-Bukhari - Abu Jamra Ad-Dabi (Sahih al-Bukhari)
I heard Ibn `Abbas (giving a verdict) when he was asked about the Mutâa with the women, and he permitted it (Nikah-al-Mutâa). On that a freed slave of his said to him, âThat is only when it is very badly needed and women are scarce.â On that, Ibn `Abbas said, âYes.â
Grade: Sahih